Proceedings of the First Joint WOSP/SIPEW International Conference on Performance Engineering 2010
DOI: 10.1145/1712605.1712634
|View full text |Cite
|
Sign up to set email alerts
|

Relating layered queueing networks and process algebra models

Abstract: This paper presents a process-algebraic interpretation of the Layered Queueing Network model. The semantics of layered multi-class servers, resource contention, multiplicity of threads and processors are mapped into a model described in the stochastic process algebra PEPA. The accuracy of the translation is validated through a case study of a distributed computer system and the numerical results are used to discuss the relative strengths and weaknesses of the different forms of analysis available in both appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 22 publications
(26 reference statements)
0
22
0
Order By: Relevance
“…A promising line of research seems to be, in the context of PEPA, the use of theoretical error probability bounds of densitydependent chains [15]. For a numerical investigation into the quality of the approximation of stiff large-scale models, the interested reader is referred to [16].…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising line of research seems to be, in the context of PEPA, the use of theoretical error probability bounds of densitydependent chains [15]. For a numerical investigation into the quality of the approximation of stiff large-scale models, the interested reader is referred to [16].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The increase in the population counts of P and Q by the same value is expressed with the same rate being present in dx 2 (t)/dt and dx 4 (t)/dt, but with opposite sign. The other summands in (17) may be obtained from analogous interpretations of the generating functions (15) and (16). A family of CTMCs {X n (t)} can be systematically associated with a PEPA model by taking a density vector, denoted by δ ∈ N d 0 , which is interpreted as giving the relative proportions between the distinct sequential components.…”
Section: Motivating Examplementioning
confidence: 99%
“…Tribastone [10] compared the solutions of LQNS and the numerical solution of the Markov chain underlying an PEPA model for a distributed system. He found a prediction error below 15 percent in most of the analyzed cases and showed that the LQN solver was orders of magnitude faster in cases with low concurrency levels.…”
Section: Quantitative Comparisonsmentioning
confidence: 99%
“…Quantitative comparisons of model transformations and/or analysis tools can be found in [9], [10], [11]. However, Balsamo et al [9] do not compare the respective solver execution times, and the comparison conducted by Tribastone et al [10], [11] does not involve model transformations as the stochastic performance models are modeled by hand.…”
Section: Introductionmentioning
confidence: 99%
“…) See for instance [40], [38] for a study of these results in software performance models expressed in a process algebra [23], and [35], [36] for an application to layered queuing networks [21].…”
Section: Definition 3 (Ode Semantics) the Ode Semantics Of A Paad (Vmentioning
confidence: 99%